2006
DOI: 10.1177/08830738060210062101
|View full text |Cite
|
Sign up to set email alerts
|

Stiripentol in Childhood Partial Epilepsy: Randomized Placebo-Controlled Trial with Enrichment and Withdrawal Design

Abstract: Stiripentol, a new antiepileptic drug inhibiting cytochrome P450-enzymes, suggested some efficacy when combined with carbamazepine in an open trial in refractory partial epilepsy of childhood. Our objective was to test these results in a placebo-controlled trial. To limit the number of patients included, we used an enrichment and withdrawal design. Among the 67 children entered in a 4-month open add-on stiripentol study following a 1-month single-blind placebo baseline, the 32 responders were randomized for 2 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
33
0
2

Year Published

2007
2007
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 50 publications
(36 citation statements)
references
References 14 publications
1
33
0
2
Order By: Relevance
“…Clobazam is demethylated to its active metabolite, Ndesmethylclobazam (norclobazam) via cytochrome P450 (CYP)3A4 and CYP2C19, which is further demethylated to an inactive metabolite by CYP2C19. Stiripentol inhibits both CYP3A4 and CYP2C19, resulting in an approximate twofold increase in clobazam, and a three-to five-fold increase in Ndesmethylclobazam In studies of efficacy and tolerability of stiripentol, adverse effects have been reported in the majority of subjects, both human and animal [27][28][29][30]. However, adverse effects were often ameliorated by reduction of concurrent medications, and discontinuation of stiripentol because of adverse effects was rare [20,28].…”
Section: Neuroprotectionmentioning
confidence: 93%
“…Clobazam is demethylated to its active metabolite, Ndesmethylclobazam (norclobazam) via cytochrome P450 (CYP)3A4 and CYP2C19, which is further demethylated to an inactive metabolite by CYP2C19. Stiripentol inhibits both CYP3A4 and CYP2C19, resulting in an approximate twofold increase in clobazam, and a three-to five-fold increase in Ndesmethylclobazam In studies of efficacy and tolerability of stiripentol, adverse effects have been reported in the majority of subjects, both human and animal [27][28][29][30]. However, adverse effects were often ameliorated by reduction of concurrent medications, and discontinuation of stiripentol because of adverse effects was rare [20,28].…”
Section: Neuroprotectionmentioning
confidence: 93%
“…4 In a third trial, STP was associated with CBZ in children with partial epilepsy using an enrichment and withdrawal design in order to limit the number of patients included. 11 Among the 67 children entered in a 3-month open add-on STP study after a 1-month single-blind placebo baseline, the 32 responders were randomized for 2 months either to continue STP (n ϭ 17) or to withdraw to placebo (n ϭ 15). If seizures increased by at least 50% after randomization compared to baseline, patients dropped out: this escape criterion was selected as the primary endpoint for this trial for ethical reasons.…”
Section: Efficacymentioning
confidence: 99%
“…Only a single patient, who was on placebo, was withdrawn from the study for adverse effects. In the controlled trial for partial epilepsy with STP-CBZ combination, 11 12 patients (71%) experienced at least one adverse event on STP, compared with 4 (27%) on placebo during the double-blind period; 9 patients (53%) experienced at least one neurological AE (drowsiness, intellectual slowness, ataxia, diplopia) versus 3 (20%) on placebo; 6 (35%) had a digestive AE (nausea, abdominal pain) on STP, but none did on placebo.…”
Section: Tolerabilitymentioning
confidence: 99%
“…Zeigte ein Patient im Vergleich zur Baseline eine Zunahme der Anfallshäufigkeit um mehr als 50%, so wurde er aus ethischen Gründen aus der laufenden Untersuchung herausgenommen. Die Datenauswertung nach Studienende ergab zwar eine Verringerung der Anfallsfrequenz in der Stiripentolgruppe um etwa 75% gegenüber 22% in der Plazebogruppe, eine statistische Relevanz konnte jedoch aufgrund der zu niedrigen Fallzahl gegen Ende der Studie nicht erreicht werden [3,4]. Weitere kontrollierte Studien bei fokalen Epilepsien liegen nicht vor.…”
Section: Stiripentol (Diacomit®) N Pharmazeutische Eigenschaftenunclassified
“…Es handelte sich bei beiden um doppelblinde, Plazebokontrollierte und randomisierte Multicenterstudien, die sich jeweils über einen Zeitraum von drei Monaten erstreckten. Sie verglichen die Wirksamkeit von Stiripentol mit Plazebo in Kombination mit Clobazam und Valproat [1][2][3][4][5].…”
Section: Stiripentol (Diacomit®) N Pharmazeutische Eigenschaftenunclassified